PENGARUH RASIO KEUANGAN DALAM MEMPREDIKSI PERUBAHAN LABA PADA PERUSAHAAN FOODS AND BEVERAGES YANG TERDAFTAR DI BEI - Nababan, Daniel; Franklin Kharism, Genta (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2019)
This research is done to analyze the influence of financial ratios in predecting of changes profit in foods and beverages listed BEI since 2015-2018 (4 years). This research used 56 samples data, the dependent variable is earning change and the independent variable are Quick Ratio, Debt to Total Assets Ratio, Debt to Equity Ratio, Total Assets Turn Over, Inventory Turn Over, Gross Profit Margin, and Net Profit Margin. The hypothesis in this researched was tested by using double regression analysis system. The result of this research is that in partial test Quick Ratio, Debt to Total Assets Ratio, Debt to Equity Ratio, Total Assets Turn Over, Inventory Turn Over, Gross Profit Margin, and Net Profit Margin given brought not significant impact in earning changes in foods and beverages listed BEI. While in simultaneously Quick Ratio, Debt to Total Assets Ratio, Debt to Equity Ratio, Total Assets Turn Over, Inventory Turn Over, Gross Profit Margin, and Net Profit Margin given brought significant impact in earning changes in foods and beverages listed BEI.